Improving Student Learning Outcomes of Cooperative Social Studies Learning Model Type of Think Pair Share (TPS) Class IV SD - didisyahrir didisyahrir; Yeni Erita; Feby Kurniawan; Vani Qhairum Nisa Utami (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Abstract Starting from the problem that: Teachers often teach lessons using the lecture method, question and answer so that students feel bored in learning. In the learning process the teacher is active while the students are passive, because student learning is more individual in nature so that the student scores are much below average. Based on the results of the research that has been carried out, it can be seen that the results of the planning cycle I meeting I was 68, meeting II increased to 82 and in cycle II meeting I became 89. The results of teacher and student activities in cycle I meeting I were 69, meeting II increased to 81 and cycle II meeting I became 93. Social studies learning outcomes for class IV SDN 15 Patamuan District can be increased by using the Think Pair Share (TPS) Type Cooperative Model. The average results of the assessment of the two aspects of assessment, namely cognitive and affective, are as follows: Cycle I, meeting I was an average of 62.81 and meeting II, the average rose to 70.93. In cycle II, social studies learning outcomes were an average of 76.87. So by using the Cooperative Model Type Think Pair Share (TPS) social studies learning outcomes of students can be increased. Keywords: learning outcomes; social studies learning; cooperative model type think pair share; SD